Correlation: Between Autochthonous Microbial Diversity and Volatile Metabolites During the Fermentation of Nongxiang Daqu - Deng, Yuke; Huang, Dan; Han, Baolin; Ning, Xinqian; Yu, Dong; Guo, Huixiang; Zou, Yufang; Jing, Wen; Luo, Huibo (Frontiers in Microbiology, 2021)
Daqu is an important saccharifying and fermenting agent. It provides various microorganisms and enzymes for the fermentation of Baijiu,and plays a vital role in the formation of Baijiu flavor. However, it is difficult to obtain the information of microbial growth and metabolism in time in Daqu production. Therefore, the "Qu Xiang" obtained by smelling is an important index in the traditional production process to evaluate the microbial fermentation in the process of Daqu-making, "Qu Xiang" mainly represents the volatile flavor compounds in Daqu. The microbial diversity and volatile metabolites on 0, 6, 16 and 29 days fermentation process were measured using high-throughput sequencing and gas chromatography–mass spectrometry. Significant differences we found that there were in the composition at microbial community. Pseudomonas, Weissella, Bacillus, and Pelomonas were the main bacterial genera. Alternaria, Rhizopus, and Pichia are the main fungal genera. A total of 32 differential volatile metabolites were detected in samples four time points using differential metabolics analysis. The correlation of dominant microorganisms with differential metabolites detected by Spearman correlation and two-way orthogonal partial least squares analysis indicated that Saccharopolyspora exhibited a significant positive correlation with the 12 differential metabolites. And there was, a significant positive correlation was observed between Rhizomucor and 13 different metabolites. These findings might help not only can help us understand the metabolism of microorganisms in Daqu fermentation more deeply but also helps to control the microorganisms in Daqu-making process, so as to obtain more stable Baijiu products.